1983
DOI: 10.1002/mrd.1120070103
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the polymorphic spermatozoa of a marine snail. 2. Genesis of the eupyrene sperm

Abstract: Spermiogenesis of the eupyrene sperm in the snail, Fusitriton oregonensis, was studied with light and electron microscopes. Endoplasmic reticulum, which encircles the nucleus in each spermatid, appears to connect with the Golgi body and to interconnect between adjacent spermatids via cytoplasmic bridges. It is suggested that as the Golgi body migrates around the nucleus the endoplasmic reticulum may circulate with it. The alignment of the proacrosome with the nucleus is effected by a 180° rotation of the Golgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
0
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 27 publications
6
37
0
1
Order By: Relevance
“…f TS of the endpiece, the axoneme is close to the membrane. an Annulus, ax axoneme, g putative glycogen granules, m mitochondrion, U U-shaped deWning edge of mitochondrial element the 'carrier type' described by Buckland-Nicks et al (1982b). We did not observe any physical association of euspermatozoa and paraspermatozoa in the testis and in the sperm duct of A. beckii.…”
Section: Paraspermatozoamentioning
confidence: 56%
“…f TS of the endpiece, the axoneme is close to the membrane. an Annulus, ax axoneme, g putative glycogen granules, m mitochondrion, U U-shaped deWning edge of mitochondrial element the 'carrier type' described by Buckland-Nicks et al (1982b). We did not observe any physical association of euspermatozoa and paraspermatozoa in the testis and in the sperm duct of A. beckii.…”
Section: Paraspermatozoamentioning
confidence: 56%
“…Paraspermatozoa produced among invertebrates are classified into three types according to nuclear conditions and developmental process: spermatozoa with no chromatin, apyrene; those with very little chromatin, oligopyrene; those with an excess of chromatin, hyperpyrene (Meves, 1903;Sivinski, 1984; although these authors did not use the term paraspermatozoa). Paraspermiogenesis of most Gastropoda occurs with no or irregular maturation division; spermatocytes transform into apyrene sperm or into diploid or polyploid sperm by asymmetrical division (see, e.g., Buckland-Nicks et al, 1982;Okura et al, 1988;Hodgson, 1997). Those paraspermatozoa are formed along with euspermatozoa and often in the same areas of the testis (Healy and Jamieson, 1981;Hodgson, 1997).…”
Section: Parapsermiogenesis and Paraspermatozoamentioning
confidence: 98%
“…The present study has revealed two types of paraspermatozoa in Campanile-one of which possesses a nuclear core (with axonemes attaching to the base of the head) and the other type lacking any apparent nuclear remnant (axonemes penetrating almost to the base of the acrosome-like structure, and evidently attaching to the blocks of the mosaic sheath). Although paraspermatozoal dimorphism has not been demonstrated in any other cerithiaceans, it is well known in viviparacean species (Yasuzumi & Tanaka, 1958;Nishiwaki, 1964;Tochimoto, 1967) and in certain other mesogastropod groups such as the Tonnacea and Epitoniacea (Nishiwaki, 1964;Tochimoto, 1967;Nishiwaki & Tochimoto, 1969;Buckland-Nicks et al, 1982). On balance, however, the paraspermatozoa of Campanile resemble those of families such as the Cerithiidae, Potamididae and also, apparently, Turritellidae (mosaic sheath of head, nuclear core [nucleate paraspermatozoa only], acrosome-like structure, tail tuft).…”
Section: Recurvature Of Euspermatozoamentioning
confidence: 99%